PERUMUSAN PERTANGGUNGJAWABAN TINDAK PIDANA KORPORASI DALAM BERBAGAI UNDANG-UNDANG - Silvia Kurnia Dewi (Arena Hukum, 2020)
AbstractThis research addresses two main points. First, the pattern of formulating criminal liability in corporate criminal acts in various laws and regulations in Indonesia. Second, the corporate criminal liability mechanism includes legal entities and non-legal entities. This is a normative research with the aim of discovering the truth of coherence. The research uses statutory and conceptual approach. The results shows that in various laws and regulations governing corporate criminal law, there are 3 groups of legal subjects that can be held liable for criminal responsibility, namely management, management and corporation, and fi nally management and/or corporation. Each group has different consequences in applying criminal sanctions. In various laws, it is also found that there are formulations of criminal sanctions in the Act which cannot be executed/ executed. The mechanism of corporate criminal liability in various laws is also not all set clearly, even there are several laws that do not mention the mechanism of corporate criminal liability.Â AbstrakPenelitian ini membahas, pertama, pola perumusan pertanggungjawaban pidana dalam tindak pidana korporasi dalam berbagai peraturan perundang-undangan di Indonesia, dan kedua, mekanisme pertanggungjawaban pidana korporasi termasuk yang berbadan hukum maupun yang bukan berbadan hukum. Penelitian hukum ini merupakan penelitian normative. Hasil dari penelitian menunjukkan bahwa dalam berbagai peraturan perundang-undangan yang mengatur pidana korporasi, terdapat 3 kelompok subjek hukum yang dapat dimintai pertanggungjawaban pidana yaitu pengurus, pengurus dan korporasi, dan terakhir pengurus dan/atau korporasi Masing-masing kelompok mempunyai konsekuensi yang berbeda dalam penerapan sanksi pidana Dalam berbagai perundangan tersebut juga ditemukan bahwa terdapat rumusan sanksi pidana dalam undang-undang yang tidak dapat dijalankan/dieksekusi Mekanisme pertanggungjawaban pidana korporasi dalam berbagai undang-undang tersebut juga tidak semua mengatur dengan jelas, bahkan terdapat beberapa undang-undang yang tidak menyebutkan mengenai mekanisme pertanggungjawaban pidana korporasi